Mortality associated with new risk classification of developing refeeding syndrome in critically ill patients: A cohort study. Issue 3 (March 2021) - Yoshida, Minoru; Izawa, Junichi; Wakatake, Haruaki; Saito, Hiroki; Kawabata, Chizu; Matsushima, Shinya; Suzuki, Aya; Nagatomi, Akiyoshi; Yoshida, Toru; Masui, Yoshihiro; Fujitani, Shigeki
Summary: Background & aims: Although refeeding syndrome (RFS) has been recognized as a potentially fatal metabolic complication, the definition of RFS has remained unclear. Recently, European researchers suggested an evidence-based and consensus-supported algorithm that consisted of a new RFS risk classification and treatment strategies for medical inpatients. The classification was based on the National Institute for Health and Clinical Excellence (NICE) criteria for patients at risk of developing RFS. In this study, we aimed to investigate the frequency of each applied new risk group and the association between the new classification and mortality in critically ill patients. Methods: This cohort study was conducted at a Japanese metropolitan tertiary-care university hospital from December 2016 to December 2018. We included critically ill adult patients who were admitted to the intensive care unit (ICU) via the emergency department and who stayed in the ICU for 24 h or longer. We applied the new risk classification based on the NICE RFS risk factors on ICU admission. The main exposure was risk classification of RFS: no risk, low risk, high risk, or very high risk. The primary outcome was in-hospital mortality censored at day 30 after ICU admission. We performed a multivariable analysis using Cox proportional hazard regression. Results: We analyzed 542 patients who met the eligibility criteria. The prevalence of the four RFS risk classification groups was 25.8% for no risk, 25.7% for low risk, 46.5% for high risk, and 2.0% for very high risk. The 30-day mortality was 5.0%, 7.2%, 16.3%, and 27.3%, respectively (log-rank trend test: p  < 0.001). In the multivariable Cox regression, adjusted hazard ratios with no risk group as a reference were 1.28 (95% CI 0.48–3.38) for low risk, 2.81 (95% CI 1.24–6.35) for high risk, and 3.17 (95% CI 0.78–12.91) for very high risk. Conclusions: Approximately half the critically ill patients were categorized as high or very high risk based on the new risk classification. Furthermore, as the risk categories progressed, the 30-day in-hospital mortality increased. Early recognition of patients at risk of developing RFS may improve patient outcomes through timely and optimal nutritional treatment.